2018
DOI: 10.1177/1538574418779466
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tibial Runoff on Outcomes of Endovascular Treatment for Femoropopliteal Atherosclerotic Lesions

Abstract: The patients with poor runoff showed significantly lower amputation-free survival and freedom from ischemia. In poor tibial runoff limbs with critical limb ischemia or tissue loss, BTK intervention did not demonstrate additional significant beneficial outcomes; however, there was a minor trend of longer lasting freedom from ischemia after concomitant BTK intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Atherosclerotic diseases may include femoropopliteal artery stenosis or occlusion. [1,2] Percutaneous transluminal angioplasty (PTA) is an effective and minimally invasive treatment strategy for atherosclerotic femoropopliteal artery stenosis/occlusion disease. [3–5] Balloon angioplasty is a widely used technique in the management of occlusive disease in almost all arterial segments.…”
Section: Introductionmentioning
confidence: 99%
“…Atherosclerotic diseases may include femoropopliteal artery stenosis or occlusion. [1,2] Percutaneous transluminal angioplasty (PTA) is an effective and minimally invasive treatment strategy for atherosclerotic femoropopliteal artery stenosis/occlusion disease. [3–5] Balloon angioplasty is a widely used technique in the management of occlusive disease in almost all arterial segments.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Certain characteristics have been demonstrated to confer higher risk of major adverse cardiovascular events (MACE) or major adverse limb events (MALE) following PVI, such as diabetes, 2 , 3 , 4 chronic kidney disease (CKD), 5 , 6 concomitant coronary artery or cerebrovascular disease, 7 , 8 and certain lesion characteristics. 2 , 9 , 10 , 11 However, the relationships between these factors have not been well explored in high‐quality, multi‐center data sets, with most reports focusing instead on the contribution of isolated high‐risk features to outcomes. 3 , 4 , 6 , 9 , 10 , 11 Other studies have described contributions of multiple risk factors, though with limited outcomes, single center data, or with minimal PAD‐ and procedure‐specific data.…”
mentioning
confidence: 99%
“… 2 , 9 , 10 , 11 However, the relationships between these factors have not been well explored in high‐quality, multi‐center data sets, with most reports focusing instead on the contribution of isolated high‐risk features to outcomes. 3 , 4 , 6 , 9 , 10 , 11 Other studies have described contributions of multiple risk factors, though with limited outcomes, single center data, or with minimal PAD‐ and procedure‐specific data. 5 , 12 , 13 , 14 , 15 This can lead to attributing risk to a comorbidity (eg, diabetes) while missing the possible intermediary steps by which that characteristic may contribute to events (for example, through the association between diabetes and worse infrapopliteal runoff).…”
mentioning
confidence: 99%
“…Prior studies have shown improved patency and limb salvage with better runoff scores. 12,13 However, most of these studies were in patients with CLTI and are not necessarily generalizable to the claudicant population where further study is required. Finally, progression to minor and/or major amputation after an intervention for IC, especially within one year, should be considered a failure of treatment and bring into question the overall indication for the initial PVI.…”
Section: Discussionmentioning
confidence: 99%